IMPROVING POST-PARTUM HEALTH USING HERBAL SOURCES - Ida Maryati; Anita Setyawati (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
The postpartum period is a time after the placenta is born until 40 days later, during this period there is a process of returning the physical condition of the mother after conceiving and giving birth. In the process of returning this physical condition requires more attention because there is a possibility of upcoming problems such as bleeding, infection, breastfeeding disorders, vascular disorders, and psychological. There have been several efforts made to support the improvement of postpartum maternal health, both using professional care and through traditional treatments such as the use of herbs. The purpose of this study was to identify the benefits of herbal medicines and their effectiveness in improving mothers’ health in the puerperium. This study used a literature review approach through search in the Google Scholar, EBSCO, and Proquest databases with keywords: herbal, post-partum, and health promotion. In this study, 12 journals were obtained regarding the use of herbs used by women in the puerperium period to improve their health. Herbs used to improve maternal health include: purple sweet potato leaves, katuk leaves, turmeric, lempuyang, tamarind, green bean extract, black meeting, aloe vera, kalendula flowers, binahong leaves, rosella flowers, bitter orange, and lavender. The use of this herb serves to help repair reproductive organs to recover as before pregnancy.Keywords: Herbal, health promotion, postpartum.